PRACTICES ADOPTED BY PRACTITIONERS FOR ANTENATAL CARE OF HIV POSITIVE PREGNANT WOMEN IN SURAT CITY - Panchal, Shaishav J; Pawar, Ajay B; R K Bansal; Patel, Prakash B; Desai, Kanan T (International Journal of Medical Research, 2013)
Background: Prevention of parent to child transmission services for HIV fails to reach most women in resource poor countries like India. The aim of present study is to know practices adopted by obstetricians for the same in HIV positive antenatal women. Methods: This was a cross sectional study where practitioners registered in Surat Obstetric and Gynaecological Society (n=204) were personally interviewed with pretested semi structured questionnaire regarding antenatal services provided to HIV positive women. Analysis was done with Epi Info 7. Results: One third of the participants did not provide care to HIV positive women and more than half never received training in HIV. Only two third were conducting pre test counselling and giving advice for correct infant feeding practices. Less than one third provided prophylaxis for opportunistic infections. One third participants knew about Highly Active Anti Retroviral Therapy and only 10% knew about Anti Retroviral drugs avoided in pregnancy. Conclusion: There is a need to develop mechanism for training and subsequent updating of knowledge of obstetricians in HIV, especially in context to antenatal care.